Evaluación de las heladas como una amenaza climática y el conocimiento ancestral de la comunidad Quindigua de La Organización Unión y Progreso, perteneciente al Cantón Guaranda. - LLumiguano Tualombo, Ines Yessenia (2021)
Frost as an environmental response to climate change has become a serious problem for indigenous communities in the Andean area due to the negative impact it causes on livelihoods, in the current anthropocene epoch, new knowledge about The management of frost, however, has been leaving aside the knowledge of our indigenous peoples, because the teaching-learning processes have been based on technique and technology rather than on the holistic conception of life and nature that our natives own. Reason why, through this project, the ancestral knowledge of the farmers of the central Quindigua community is known and how, based on these, they respond to frost events. In the development of the research, the methodology used corresponds to a mixed investigation, which through a semi-structured interview a small description of the ancestral knowledge that the community's inhabitants have is made here, emphasis is placed on the deductive method that its The purpose is to give importance to citizen opinions, followed by this, the weighted index of frost danger allows identifying the areas that are exposed to different levels of threat, the description of precipitation and temperature allows knowing the rainy months and the dry season Finally, adaptation measures are needed to active and passive frosts according to the context and the management capacity of the community.